ANALISA PENGARUH VARIASI LAPISAN PLAT PADA PIPA SEJAJAR TERHADAP EFEKTIFITAS PENYERAPAN PANAS KOLEKTOR SURYA UNTUK PEMANAS AIR DENGAN SISTEM EFEK TERMOSIFON - Eddy Elfiano; M. Natsir Darin; M. Nizar (Universitas Pasir Pengaraian, 2013)
The sun is a source of alternative energy that is not polluting and can be used either directly or indirectly. Based on that we can use the energy of sunlight to heat water system with thermosiphon effects, by using a means of collecting solar radiation (solar collector) which absorbs the radiation and convert into heat through the absorber plate and forwarded to a pipe containing water. Absorber plate layer affects the effectiveness of the absorption of solar heat collectors. Solar collector is analyzed in the variation of the absorber plate layer on the parallel pipe, absorber plate is positioned above and below the parallel pipeline. Experiment conducted starting at 9:00 am to 15:00 pm. Effectiveness of heat absorption is obtained by using a layer under the parallel pipe plate at 11.2%, while for the layers above and below the plate parallel pipelines reached 17.8%. Differences in the efficiency of the obtained results that the use of layers above and below the absorber plate parallel pipeline more effectively.